A Balancing Act During Covid-19: Teachers' Self-Efficacy, Perception of Stress in the Distance Learning Experience - Rabaglietti, Emanuela; Lattke, Lynda S.; Tesauri, Beatrice; Settanni, Michele; De Lorenzo, Aurelia (Frontiers in Psychology, 2021)
One of the many drastic changes caused by Covid-19 was the quick implementation of distance learning which represented a great technological challenge to many teachers and students. In fact, Italy ranks 24th amongst the 27-EU member countries in digital competitiveness which testifies to the significant delays and gaps in basic digital skills amongst the population. Based on the difficulties encountered in organizing distance learning, we assumed that teachers' perceived stress increased. Given that transversal skills can be associated with this relationship, we hypothesized that among these skills, self-efficacy mediated the relationship between the difficulties in organizing distance learning and perceived stress. Since we targeted teachers from Italy and other European countries, we also hypothesized that this mediator effect would be different for both samples. Our sample was composed of a total of 366 primary/middle school teachers of which 86% female. After doing a mediation analyses with Process, Hayes' Model 4, we confirmed H1 but not H2: resulting in a partial mediation effect of self-efficacy for each individual group of teachers. Since difficulties of distance learning can affect the perception of stress, we believe that the promotion of transversal skills, such as self-efficacy, can better equip teachers when facing stressful situations.